The art of Maquis: makeup and making up in Ouagadougou, Burkina Faso - Sanogo, Senanta Fanidh (Social Anthropology, 2022)
This story is about the art of maquis among women in Ouagadougou, Burkina Faso. The thesis frames the art of maquis as a navigational technique through which women embody their aspirational self. Here, I conceptualize the art of maquis through the notions of makeup and making up. The women I worked with used makeup framed as a concept and a practice, where making up is considered the practice through which the art of maquis is performed. Here, the tools women employ to beautify their lives are discussed in terms of technologies of visibility and behavioural techniques such as flatter [to flatter]. This monograph examines how women constantly navigate opportunities by embodying their aspirations and intersubjectivity through an ethnographic analysis of makeup and making up practices in a maquis [local pub]. To navigating precarious conditions and the materiality of the contexts, the women I worked with used makeup for pragmatic reasons, often to access aspirations in the form of socio-economic capital (making up). Experts at the art of maquis (makeup and making up), these women use their bodily capital and technologies of visibility to attract and navigate opportunities in a world where they find themselves at the margins of global capitalism. Ultimately, focusing on eye and skin makeup, this ethnography of facial and behavioural adornment showcases how people aspire to be happy through technologies of visibility and the presentation of self in everyday life. The thesis suggests that studying adornment techniques from and through the maquis provides a nuanced way of theorizing the kaleidoscopic epistemologies informing gender constructions, contemporary beauty ideals and female agency in Ouagadougou.